Changes in Haematological Indices, Blood Viscosity and Inhibitors of Coagulation during Treatment of Endometriosis with Danazol - Ford, I; Li, C; Cooke, I D; Preston, F E (Thrombosis and Haemostasis, 1994)
The effects of treatment with danazol (600 mg daily) on haemostatic and haematological function were investigated in 18 pre-menopausal women with endometriosis. Blood samples were taken at 2 pre-treatment visits, at 6, 12 and 24 weeks on treatment, and at 6 weeks after discontinuation of the drug. Haemoglobin, red cell count, haematocrit and platelet count all rose significantly during treatment with danazol (p <0.01 vs. baseline). Plasma fibrinogen levels fell significantly (p <0.01), while whole blood viscosity increased during treatment and remained significantly elevated at follow-up. The prothrombin time shortened, but remained within normal limits, and there were no significant changes in factor VII:C, Vila, or fibrinopeptide A. No significant changes were found in platelet function. Plasma B-beta 15-42 increased significantly. Functional levels of protein C, protein S, and antithrombin III, all rose significantly, above the normal range, while C4b-binding protein levels fell. We conclude that the observed changes in coagulation inhibitors and fibrinolytic activity may be considered beneficial in the context of venous thromboembolism. The rheological effects, however, indicate a degree of caution in the use of the drug in individuals considered to be at risk from arterial cardiovascular disease.